2013
DOI: 10.1021/bi400119v
|View full text |Cite
|
Sign up to set email alerts
|

Functional Rotation Induced by Alternating Protonation States in the Multidrug Transporter AcrB: All-Atom Molecular Dynamics Simulations

Abstract: The multidrug transporter AcrB actively exports a wide variety of noxious compounds using proton-motive force as an energy source in Gram-negative bacteria. AcrB adopts an asymmetric structure comprising three protomers with different conformations that are sequentially converted during drug export; these cyclic conformational changes during drug export are referred to as functional rotation. To investigate functional rotation driven by proton-motive force, all-atom molecular dynamics simulations were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(89 citation statements)
references
References 51 publications
16
73
0
Order By: Relevance
“…R2 helices collectively rotate about R1 in the anti-clockwise direction on the membrane plane (Fig. 8a), resembling the O-to-L transition revealed by the crystal structures and discussed by Eicher et al 19 Such backbone movements were not reported by the previous all-atom simulations; 19,25 however, similar motion has been observed in the most recent hybrid coarse-grained simulations. 42 Along with the backbone changes, the sidechains of essential residues, Asp407, Asp408, Lys940, Thr978 and Arg941 rearrange, which leads to, among others, the movement of Lys940 from Thr978 to Asp408.…”
Section: Concluding Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…R2 helices collectively rotate about R1 in the anti-clockwise direction on the membrane plane (Fig. 8a), resembling the O-to-L transition revealed by the crystal structures and discussed by Eicher et al 19 Such backbone movements were not reported by the previous all-atom simulations; 19,25 however, similar motion has been observed in the most recent hybrid coarse-grained simulations. 42 Along with the backbone changes, the sidechains of essential residues, Asp407, Asp408, Lys940, Thr978 and Arg941 rearrange, which leads to, among others, the movement of Lys940 from Thr978 to Asp408.…”
Section: Concluding Discussionsupporting
confidence: 75%
“…The two proton model however contradicts another recent MD study which showed that protonation of both Asp407 and Asp408 destabilizes the O state. 25 By testing a combination of protonation states of Asp407/Asp408 for the O protomer, the latter study supported a one proton model, in which protonation and deprotonation of Asp408 alone drives the conformational cycling of AcrB. 25 …”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The carboxyl group of Asp408 was indeed shown to have an unusually high pK a of 7.4, which would help in the facile binding and release of the proton under physiological conditions (107). A recent MD simulation study (108) suggests that in the extrusion protomer, Asp408 becomes protonated, but Asp407 remains deprotonated. In this scheme, the translocation of one proton across the IM would be sufficient to cause the conformational changes in AcrB, resulting in the extrusion of the drug molecule(s).…”
Section: Figmentioning
confidence: 98%